Financial Health and Share Price Movements: Analysis of Wholesale Microfinance Firms - Thapa, Bhim Kumar; Paudel, Ramesh Rasik (KIC International Journal of Social Science and Management, 2024)
This research investigates the financial dynamics and share price movements of wholesale microfinance firms through a comprehensive analysis of key financial variables. The study begins with a detailed descriptive exploration, revealing significant variability in market prices, dividends, earnings, net worth, and valuation metrics among the studied firms.Correlation analyses provide nuanced insights, indicating positive associations between market prices and net worth, earnings, and earnings multiples, while revealing potential conflicts with asset-based financial performance. The research employs regression analysis to discern the impact of financial variables on market prices. Findings indicate a statistically significant positive association between Earnings per Share (EPS) and Market Price per Share (MPS), suggesting that increases in earnings per share are associated with higher market prices. However, Dividends per Share (DPS) does not exhibit a statistically significant relationship with MPS. Notably, a negative association between Return on Assets (ROA) and MPS suggests that lower returns on assets are linked to higher market prices. The Price-to-Earnings Ratio (PE) demonstrates a highly significant positive influence on MPS, emphasizing the impact of earnings multiples on market valuation. While Net Worth per Share (NWPS) and Net Profit Margin (NPM) do not exhibit statistically significant relationships with MPS, the overall regression model proves highly significant, explaining approximately 93% of the variation in market prices. The adjusted R-squared, accounting for the number of variables, is 0.91. The constant term in the regression equation indicates an intercept when all independent variables are zero. This research offers valuable insights into the factors influencing the financial health and share price movements of wholesale microfinance firms.